TRADISI MENYANGGAM UNTUK MENDAPATKAN ANAK PERSPEKTIF HUKUM ISLAM - M Azif; Irma Suryani (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
This study discusses the view of Islamic law, namely fikih / opinion of the imam of the school towards the tradition of menyanggam to get children. In the implementation of the tradition of menyanggam there is a provision that, for 2 years the borrowed child should not meet with both parents. This will have a devastating impact on parents and children. The form of implementation of the tradition of menyanggam is the habit of borrowing children from dunsanak and others, aged 2 to 5 years, fostered and treated like their own children for 2 years with the aim of getting children. In Islamic law, the tradition of menyanggam should not be done because there is an element of separating the child from his biological parents, thus adversely affecting the child and his parents. However, it is permissible to do if the preservation contained in the tradition of menyanggam is eliminated, that is, the element of separating the child from both parents.